Interdependence of neural network dysfunction and microglial alterations in Alzheimer’s disease-related models - Melanie Das (Elsevier, 2021)
Summary: Nonconvulsive epileptiform activity and microglial alterations have been detected in people with Alzheimer’s disease (AD) and related mouse models. However, the relationship between these abnormalities remains to be elucidated. We suppressed epileptiform activity by treatment with the antiepileptic drug levetiracetam or by genetic ablation of tau and found that these interventions reversed or prevented aberrant microglial gene expression in brain tissues of aged human amyloid precursor protein transgenic mice, which simulate several key aspects of AD. The most robustly modulated genes included multiple factors previously implicated in AD pathogenesis, including TREM2, the hypofunction of which increases disease risk. Genetic reduction of TREM2 exacerbated epileptiform activity after mice were injected with kainate. We conclude that AD-related epileptiform activity markedly changes the molecular profile of microglia, inducing both maladaptive and adaptive alterations in their activities. Increased expression of TREM2 seems to support microglial activities that counteract this type of network dysfunction.